Oppression and Revolt in Ancient Palestine: The Evidence in Jewish Literature from the Prophets to Josephus - Lang, Graeme (Sociological analysis, 1989)
Few ancient civilizations preserved in their literature such a lengthy tradition of tension between rich and poor, or such vivid critiques of oppression, as were preserved in the literature of Judaism. These tensions appear in both pre-exilic and post-exilic works, and surface again in some parts of the New Testament, particularly in the book of James, in passages which reflect the traditions in which Jewish Christianity was apparently grounded. The culmination of this antagonism occurred during the war of 66–70 A.D., when factions among the Jewish rebels attacked their own upper classes during the revolt against Rome. The paper documents this antagonism, and also suggests how religion and politics intermixed to produce during most of this period results quite unlike secular class-based movements. Modern thinkers and activists, in contemplating the ancient Jewish homilies and diatribes stimulated by oppression and by the plight of the lower orders in society, should note both the prevalence of this kind of material, and the constraints on its political realization in that context.